Intrauterine Hyperglycemia Alters the Metabolomic Profile in Fetal Mouse Pancreas in a Gender-Specific Manner - Zhu, Hong; Luo, Si-Si; Cheng, Yi; Yan, Yi-Shang; Zou, Ke-Xin; Ding, Guo-Lian; Jin, Li; Huang, He-Feng (Frontiers in Endocrinology, 2021)
Emerging evidence suggests intrauterine hyperglycemia exposures during critical windows of development may contribute to the increasing prevalence of diabetes. However, little is known about the maternal mechanisms responsible for offspring metabolic disorder. In this study, we investigated the intrauterine hyperglycemia exposure on fetal pancreatic metabolome, and its potential link to impaired glucose tolerance in adult offspring. Here, using a GDM mouse model, we found that the metabolome profiling of pancreas from male and female fetus showing altered metabolites in several important pathways, including 5-methylcytosine, α-KG, branched-chain amino acids, and cystine, which are associated with epigenetic modification, insulin secretion and intracellular redox status, respectively. This finding suggests that intrauterine exposure to hyperglycemia could cause altered metabolome in pancreas, which might be a metabolism-mediated mechanism for GDM-induced intergenerational diabetes predisposition.